Overall survival analysis of the FOXFIRE prospective randomized studies of first-line selective internal radiotherapy (SIRT) in patients with liver metastases from colorectal cancer - Virdee, P (American Society of Clinical Oncology, 2017)
The FOXFIRE, SIRFLOX and FOXFIRE-Global (FF-SF-FFG) randomized studies evaluated the efficacy of combining first-line chemotherapy for metastatic colorectal cancer (mCRC) with selective internal radiotherapy (SIRT) using yttrium-90 resin microspheres in patients with liver metastases. The studies were designed for prospective, combined analysis of overall survival (OS).